The love for kimchi : Korean transnational migrants, consciousness, health, and foodways. - Yuin, Freda Yu Wei. (2009)
This research paper seeks to gain an insight into the consciousness of Korean transnational migrants in relation to the foodways they practice in Singapore. For a period of 5 months beginning in late August 2008, data on Korean transnational migrants and their foodways were collected through semi-structured interviews with 16 Korean transnational migrants who have been in Singapore for at least a year. Participant observation was also conducted during weekly sleepovers at a “Korean homestay.” Analysis of data collected reveals, with regard to foodways, Korean transnational migrants operate on two levels of consciousness, first, “habitus” (Bourdieu 2002:272) , which operates at the level of the ‘unconscious’ and secondly, cultural consciousness, that considers cultural identity in cross-cultural or cross-national social interactions. This paper sees food choice as relative and questions the essentialist view that draws a direct correlation between foodways and national and/or cultural identities neglecting contextualized and interactional dimensions of food consumption and identity and the influence cross-cultural interactions have on the kinds of food choices made.